Educational Interventions and Digital Innovation for Improving BPJS Inpatient Claims - Maulia, Putri; Sartika , Iik; Ani, Nur; Rahardjo, Budhi (Universitas Negeri Semarang, 2025)
Pending inpatient claims under Indonesia’s National Health Insurance (BPJS Kesehatan) have become a critical concern for hospital financial management and administrative performance, particularly as hospitals transition to digital claim systems. This study aims to investigate the effectiveness of educational interventions and digital innovation in reducing pending BPJS inpatient claims, while providing actionable policy insights to improve hospital claim management. Employing a descriptive quantitative approach, the research utilizes secondary data from all inpatient claim submissions at RS Slamet Riyadi Surakarta for October 2024, complemented by internal audits and stakeholder interviews. The urgency of this study arises from the persistent delays in claim processing, which threaten both hospital cash flow and service sustainability. The findings reveal that inaccurate medical records constitute the most significant factor contributing to claim delays, accounting for 75% of pending cases, followed by incomplete documentation, insufficient supporting examinations, and inadequate therapeutic evidence. Novelty emerges through the systematic prioritization of delay determinants and the application of structured educational interventions and AI-based digital tools to enhance staff competence and verification processes. The research contributes practical recommendations for integrating ongoing education, digital verification, and collaborative policy-making, thereby strengthening the quality, transparency, and efficiency of BPJS inpatient claim management in Indonesian hospitals.